Current-driven nonequilibrium electrodynamics in graphene revealed by nano-infrared imaging - Y. Dong; Z. Sun; I. Y. Phinney; D. Sun; T. I. Andersen; L. Xiong; Y. Shao; S. Zhang; Andrey Rikhter; S. Liu; P. Jarillo-Herrero; P. Kim; et al. (Nature Communications)
Abstract Electrons in low-dimensional materials driven out of equilibrium by a strong electric field exhibit intriguing effects that have direct analogues in high-energy physics. In this work we demonstrate that two of these effects can be observed in graphene, leading to relevant implications for light-matter interactions at the nanoscale. For doped graphene, the Cherenkov emission of phonons caused by the fast flow of out-of-equilibrium electrons was found to induce direction-dependent asymmetric plasmon damping and an unexpected generation of photocurrent. For graphene close to charge neutrality, incident infrared photons were found to disrupt the creation-recombination balance of electron-hole pairs enabled by the condensed matter version of the Schwinger effect, resulting in an excess photocurrent that we term Schwinger photocurrent. Both Schwinger and Cherenkov photocurrents are different from other known light-to-current down conversions scenarios and thus expand the family of photoelectric effects in solid state devices. Through nano-infrared imaging methodology, we provide a more comprehensive view of current-driven nonequilibrium electrodynamics in graphene.